Down's/Turner's mosaicism. Double aneuploidy as a rare cause of missed prenatal diagnosis of chromosomal abnormality. Issue 12 (December 1981) - MacFaul, R; Turner, T; Mason, M K
Abstract : Two babies with Down's/Turner's mosaic karyotype are reported. In each, because of advanced maternal age, chromosomal analysis had been carried out on the fluid obtained by amniocentesis in early pregnancy. Only the 46, X+ 21 cell line grew in the specimens and the extra 21 chromosome was wrongly identified as a Y chromosome, so that the fetus was thought to have a normal male karyotype, 46, XY. At birth both babies were phenotypically female with features predominantly of Down's syndrome and the correct karyotype was then identified. Twenty cases of this rare chromosomal abnormality are reviewed and one other living child who had been similarly wrongly diagnosed is reported.